A policy content analysis for evaluating urban adaptation justice in Istanbul - (:unkn) unknown (My University, 2022)
Climate change is disproportionately affecting vulnerable communities, increasing existing risks and leading to further global inequalities. Drawing on the concept of urban adaptation justice, we evaluated the inclusion of vulnerable communities in the climate change adaptation planning process of ?Istanbul, a European coastal megacity with considerable vulnerability to climate change. For this, a policy content analysis structured around four criteria: (i) participation, (ii) capacity enhancement, (iii) governance, and (iv) justice integration into spatial planning, was carried out and supplemented by local expert consultations. Our findings indicate that while the objective of incorporating some aspects of justice in adaptation planning was recognized, there was a distinct lack of specific actions or evaluation tools. The expert consultations largely confirmed these findings, which were then connected to the socio-historical and political context of ?Istanbul and the wider Turkish region. Key con-clusions include the failure of current adaptation policies to adequately consider vulnerabilities arising from a combination of urban marginalization interacting with neoliberal authoritarianism. We identify the need for understanding and integrating equitable climate change adaptation as a key dimension of urban decision-making for future policy-relevant research and practice.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Su Bilimi; Fizik Bilimleri; Yaşam Bilimleri; Nature and Landscape Conservation; Environmental Science (miscellaneous); Aquatic Science; Physical Sciences; Life Sciences; Policy content analysis; Vulnerability; Urban climate justice; Adaptation; Urban inequality; Istanbul; CLIMATE-CHANGE; DECISION-MAKING; POLITICS; EQUITY; GOVERNMENT; DISCOURSE; FRAMEWORK; BARRIERS; CITIES; STATE